THE ROLE OF QUALITY CONTROL ON THE FORMATION OF AUDITOR’S PROFESSIONAL SKEPTICISM (Jurnal Dinamika Akuntansi, 2022)
AbstractPurpose: This study aimed to determine the ability of quality control to moderate the relationship between time pressure, locus of control, and professional skepticism of auditors. Method: The population included auditors in the city of Semarang, Indonesia. Data were collected using questionnaires distributed to 100 respondents with only 78 returned while the hypotheses were tested through the use of multiple regression methods.Findings: The results showed two hypotheses, the first and third, were not accepted. This, therefore, means time pressure does not affect professional skepticism and there was no moderating effect of quality control on this relationship. The remaining two hypotheses, second and fourth, were accepted. This indicates there was an influence of external locus of control on professional skepticism and quality control was able to moderate this effect.Novelty: The research’s originality was the use of Professional Skepticism variable which is made up of ethical dilemmas, knowledge and experience gap, deadline pressure, auditor characteristic, and feedback. However, several situational factors like the quality control are usually adopted in a public accounting firm as a moderating variable to improve the direct effect of certain determinants on professional skepticism Keywords: Professional skepticism, Time pressure, Locus of Control, Quality Control